1998
DOI: 10.1002/(sici)1522-7189(199802)6:1<35::aid-nt7>3.3.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Biological activities of prymnesin-2 isolated from a red tide alga Prymnesium parvum

Abstract: Previously we isolated prymnesin-1 (PRM1) and prymnesin-2 (PRM2) as the major hemolytic and ichthyotoxic agents in the red tide organism Prymnesium parvum and disclosed the structure of PRM2 as a novel glycoside with unusual multiple functionality. PRM2 caused 50% hemolysis of a 1% suspension of dog red blood cells at 0.5 nM. The potency exceeded that of plant saponin by 50000 times. The lethality of PRM2 on freshwater fish Tanichthys albonubes was comparable to that of brevetoxin and also the ichthyotoxicity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
1
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(57 citation statements)
references
References 14 publications
1
54
1
1
Order By: Relevance
“…The toxins produced by Prymnesium cells are also known to act on cell membranes and disrupt the ability of selective permeability (Shilo 1967), which Meldahl et al (1996) thought was probably due to an influx of Ca 2 . However, recent studies by Igarashi et al (1998), have shown that the haemolytic activity of prymnesins are not affected by Ca 2 but by the origen of the blood cell being tested. Several studies have shown that Prymnesium toxins damage cell membranes and exert lytic effects on various cell types including blood cells, human liver cells and amnion cells (Shilo & Rosenberger 1960, Meldahl & Fonnum 1993, Johansson & Granéli 1999, Granéli & Johansson 2003).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The toxins produced by Prymnesium cells are also known to act on cell membranes and disrupt the ability of selective permeability (Shilo 1967), which Meldahl et al (1996) thought was probably due to an influx of Ca 2 . However, recent studies by Igarashi et al (1998), have shown that the haemolytic activity of prymnesins are not affected by Ca 2 but by the origen of the blood cell being tested. Several studies have shown that Prymnesium toxins damage cell membranes and exert lytic effects on various cell types including blood cells, human liver cells and amnion cells (Shilo & Rosenberger 1960, Meldahl & Fonnum 1993, Johansson & Granéli 1999, Granéli & Johansson 2003).…”
Section: Discussionmentioning
confidence: 97%
“…Prior to the growth experiment, the toxicity of Prymnesium parvum cultures grown under different nutrient conditions was tested using an Artemia-assay. The reason to use this test is because, although some of the toxins are identified (see Igarashi et al 1998, Sasaki et al 2001), a chemical method will only be possible after all the toxins have been identified. Eggs of A. salina (Mackay Marine Brine Shrimp) were hatched according to Vanhaecke et al (1981) using filtered (90 mm membrane filter [Gelman Science] mesh size 0.45 µm) autoclaved seawater with a salinity of 7 ‰ and pH 8.0.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Intracellular toxicity of Prymnesium parvum was measured using horse red blood cells (Igarashi et al 1998). Saponin was used to produce a standard hemolytic curve for reference.…”
Section: Intracellular Toxicitymentioning
confidence: 99%
“…The polyoxy-polyene-polyether toxins prymnesin 1 and 2 produced by the prymnesiophyte Prymnesium parvum (Igarashi et al, 1998) are believed to perforate cell membranes of other cells, and can even cause fish kills. Similarly, glycosylglycerolipids with ichthyotoxic and hemolytic potential were found in the fish-killing prymnesiophyte Chrysochromulina polylepis and the dinoflagellate Karenia mikimotoi (Yasumoto et al, 1990).…”
Section: Introductionmentioning
confidence: 99%